TINJAUAN YURIDIS WANPRESTASI DALAM PERJANJIAN KREDIT DENGAN JAMINAN PERSEORANGAN - Halitatur Rahmaniyah; Sumriyah (JOURNAL SAINS STUDENT RESEARCH, 2023)
Credit agreements in the context of Indonesian civil law with a focus on aspects such as good faith, balance of rights and obligations, and principles of justice. This research explores how credit agreements act as the main instrument in lending and borrowing transactions between banks and other parties. One of the key aspects studied in this journal is default, where the debtor is unable to fulfill obligations such as paying interest rates or repaying loans. This research also discusses individual guarantees, both in the form of guarantees and underwriting, as a mechanism to protect creditors from the risk of loss due to debtor default. defaults can occur, and an in-depth exploration of the role of personal guarantees in protecting creditors. Based on the results of this research, it provides valuable insights for parties involved in financial transactions, and legal researchers who are interested in the dynamics of civil law related to credit agreements, defaults and personal guarantees.